Logical Relations according to De Beauvoir and Their Impact on Achieving Textual Coherence (Usul Al-Kafi as a Model) - Isfahani , Dr. Mohammad Khaqhani; Al-Eidani, Prof Dr. Jalal Al-Din Yousif; Ajeel, Musa Jasim (Thi Qar Arts Journal, 2023)
Semantic relationships are the concepts carried by the syntactic structures of the text and are an important axis of textual relationships. The continuity and coherence of the text presupposes the existence of this type of relationship between the parts of the text and determines its appearance and unity. Each language has syntactic systems that work towards the text to control them to give different meanings. They work to gather the ends of the text in a sequential form, and the difference between semantic relationships is due to the difference in syntactic structures in the text, and some surface structures work to highlight meanings in the form of semantic relationships that reveal the meaning of the text and the main purpose for which these relationships were established, and relationships may differ in terms of some of them relying on clear linguistic links in the apparent text, as they are sometimes external relationships that the recipient imposes on the text, not the text itself, and are a result of textual phenomena such as advancement, delay, and pronoun references. There are relationships that become clear through conjunctions that connect sentences, or through referential elements. Relationships represent links for concepts that work to continue meanings in the fabric of the text through exchange between sender and recipient. Every text that is issued from producer to recipient is not free from these relationships, and these relationships take place within an organizational framework governed by the intention of the speaker and the other party, readers. In Kafi's conversations, we find that Al-Maqam relies on the semantic dimension in the process of coherence of texts.